Hyperthermia and biological investigation of a novel magnetic nanobiocomposite based on acacia gum-silk fibroin hydrogel embedded with poly vinyl alcohol - Zeinab Pajoum; Hooman Aghamirza Moghim Aliabadi; Adibeh Mohammadi; Zahra Sadat; Amir Kashtiaray; Milad Salimi Bani; Mohammadali Shahiri; Mohammad Mahdavi; Reza Eivazzadeh-Keihan; Ali Maleki; Majid M. Heravi (Heliyon)
The design and synthesis of biocompatible nanostructures for biomedical applications are considered vital challenges. Herein, a nanobiocomposite based on acacia hydrogel, natural silk fibroin protein, and synthetic protein fibers of polyvinyl alcohol was fabricated and magnetized with iron oxide nanoparticles (Fe3O4 MNPs). The structural properties of the hybrid nanobiocomposite were investigated by essential analyses such as Fourier Transform Infrared Spectrometer (FTIR), Field emission scanning electron microscopy (FE-SEM), and X-ray powder diffraction)XRD(analyses, Thermogravimetric and Differential thermogravimetric analysis (TGA-DTG), Vibrating-sample magnetometry (VSM), and Energy Dispersive X-Ray Analysis (EDX). The biological activities and functional properties of the prepared magnetic nanobiocomposite were studied. Results proved that this nanobiocomposite is non-toxic to the healthy HEK293T cell line. In addition, the synthesized nanobiocomposite showed an approximately 22 % reduction in cell viability of BT549 cells after 72 h. All results confirmed the anti-cancer properties of nanobiocomposite against breast cancer cell lines. Therefore, the prepared nanobiocomposite is an excellent material that can use for in-vivo application. Finally, the hyperthermia application was evaluated for this nanobiocomposite. The SAR was measured 93.08 (W/g) at 100 kHz.